New Records of Sharpshooters (Hemiptera, Cicadellidae, Cicadellinae) in Citrus Orchards in Amazonas State, Brazil - Paola Victoria Moreno Franco; Joyce Adriana Froza; Nathalia Hiluy Pecly; João Roberto Spotti Lopes; Jânia Lilia da Silva Bentes Lima; Agno Nonato Serrão Acioli (Insects, 2024)
This research study reports new records of eight species of Cicadellini (Hemiptera, Cicadellidae, Cicadellinae) across seven municipalities in Amazonas State, Brazil. Among these species, one is known as a vector of CVC (Provancherana corniculata). Additionally, five species are being reported for the first time in citrus for the State (Erythrogonia sexguttata, Hortensia similis, Provancherana corniculata, Scopogonalia amazonensis, and Scoposcartula oculata), and three species (Diedrocephala variegata, Macugonalia moesta and Xyphon reticulatum) are reported for the first time in the northern region. This research highlights the lack of information on sharpshooter occurrence in the Amazonas region, emphasizing the need for further investigations in this area.